Laporan Kasus Hiperleukositosis pada Pasien Anak 7 Bulan dengan Akut Limfoblastik Leukimia (ALL) Tipe L1 - Rogatianus Bagus; Ghazlina Winanda (Medula, 2020)
Acute lymphoblastic leukemia (ALL) type L1 patients are the most common type found in hematolymphopoietic neoplasms. Reportedly a child aged 7 months with complaints of fever and pale. Physical examination showed hepatosplenomegaly. Investigations found an increase in leukocytes of 285,000 / µL. The results of Leukemia Phenotyping examination showed that leukemia types included ALL type L1, immunotyping showed precusor B cell, there was no gene fusion examination. Treatment for 3 days at Type A Hospital to find the right diagnosis and improve the general condition of the patient. Therapy can be given earlu and adequate for the provision of hyperlaucocytosis with aggressive hydration, alkalinization of urine and will be given chemotherapy drugs supported by stable general patients such as anemia, thrombocytopenia or leukocytosis and hyperleukocytosis. if the patient's general condition is stable, such as anemia, thrombocytopenia or leukocytosis or even hyperleukocytosis. If the patient's condition is stable, initiation of chemotherapy treatment can be started according to the Indonesian protocol ALL HR 2018. This protocol consists of an induction phase for 6 weeks, consolidation for 4 weeks, reinduction for 4 weeks, and a maintenance phase of up to 110 weeks.